Bone marrow mesenchymal stromal cells induce nitric oxide synthase-dependent differentiation of CD11b(+) cells that expedite hematopoietic recovery - Trento, Cristina (Haematologica, 2017)
Bone marrow microenvironment is fundamental for hematopoietic homeostasis. Numerous efforts have been made to reproduce or manipulate its activity to facilitate engraftment after hematopoietic stem cell transplantation but clinical results remain unconvincing. This probably reflects the complexity of the hematopoietic niche. Recent data have demonstrated the fundamental role of stromal and myeloid cells in regulating hematopoietic stem cell self-renewal and mobilization in the bone marrow. In this study we unveil a novel interaction by which bone marrow mesenchymal stromal cells induce the rapid differentiation of CD11b(+) myeloid cells from bone marrow progenitors. Such an activity requires the expression of nitric oxide synthase-2. Importantly, the administration of these mesenchymal stromal cell-educated CD11b(+) cells accelerates hematopoietic reconstitution in bone marrow transplant recipients. We conclude that the liaison between mesenchymal stromal cells and myeloid cells is fundamental in hematopoietic homeostasis and suggests that it can be harnessed in clinical transplantation.